PEWARISAN DZAWIL ARHAM BERSAMA ASHABUL FURUDH (Analisis Terhadap Putusan Pengadilan Tinggi Agama Bangka Belitung No. 4/Pdt.G/2020/PTA.BB) - Khotimah, Khusnul (Al-Ahwal Al-Syakhsiyyah: Jurnal Hukum Keluarga dan Peradilan Islam, 2022)
This research was motivated by the decision of the Bangka Belitung Religious High Court No.4/Pdt.G/2020/PTA.BB decided on the inheritance case, which in the decision decided that the heirs of dzawil arham got a share of the inheritance when he was with the heirs of dzawil furudh. Whereas the provisions of dzawil arham get the inheritance from the heir when the heirs of ashabul furud and ashabah are not present. This thesis is the result of a research entitled "The Inheritance of Dzawil Arham with Ashabul Furudh (Analysis of the Decision of the Bangka Belitung Religious High Court No.4/Pdt.G/2020/PTA.BB)". This study aims to: a) explain the results of the decision of the Religious High Court of Bangka Belitung No. 4/Pdt.G/2020/PTA.BB regarding the Inheritance of Dzawil Arham with Ashabul Furud. b) knowing the reasons for the judges of the Bangka Belitung Religious High Court in deciding case No. 4/Pdt.G/2020/PTA.BB regarding the Inheritance of Dzawil Arham with Ashabul Furud. c) analyze the decision of the Bangka Belitung Religious High Court No. 4/Pdt.G/2020/PTA.BB regarding the Inheritance of Dzawil Arham with Ashabul Furud. Â Â This research uses a qualitative approach by using a case study research approach. The type of research used in this research is field research, namely examining the case at the Bangka Belitung Religious High Court with the decision no. 4/Pdt.G2020/PTA.BB. Sources of data are taken from books and literature related to the problems in the research. The data collection technique was carried out by the methods of observation, interviews, document review and content analysis. Data analysis using documentation method. Â Â The results of the study indicate that the decision of the judges of the Bangka Belitung Religious High Court in case No.4/Pdt.G/2020/PTA. BB decided that the heirs of dzawil arham would still get the inheritance even when he was with the heirs of dzawil furudh. As for the share of each of the heirs' inheritance, namely Dzawil Furudh and Dzawil Arham, they both get 2/6 shares and this distribution is based on rad. Furthermore, the reason for the judge of the Bangka Belitung Religious High Court in deciding case No. 4/Pdt.G/2020/PTA.BB regarding the inheritance of dzawil arham with ashabul furud is based on the principle of balanced justice, namely that between men and women get the same rights in the distribution of assets. inheritance. Not only that, the reason for the panel of judges in determining the share of inheritance to the grandfather from the mother's side, namely the heirs of Dzawil Arham, got the inheritance because during his life the heir lived with his maternal grandfather besides his parents. In addition, the judge also reasoned that the heir and heirs have closeness and kinship. Therefore, the panel of judges of the Bangka Belitung Religious High Court gave a share to the heirs of Dzawil Arham. Keywords: Inheritance, Dzawil Arham, Ashabul Furudh